2010
DOI: 10.1111/j.1750-3841.2009.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Active Packaging of Fresh Chicken Breast, with Allyl Isothiocyanate (AITC) in Combination with Modified Atmosphere Packaging (MAP) to Control the Growth of Pathogens

Abstract: Listeria monocytogenes and Salmonella typhimurium are major bacterial pathogens associated with poultry products. Ally isothiocyanate (AITC), a natural antimicrobial compound, is reportedly effective against these pathogenic organisms. A device was designed for the controlled release of AITC with modified atmosphere packaging (MAP), and then evaluated for its ability to control the growth of L. monocytogenes and S. typhimurium on raw chicken breast during refrigerated storage. In order to obtain controlled rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…In particular, it has been demonstrated that allyl ITC (AITC), which is formed from sinigrin (2-propenyl glucosinolate), effectively inhibits a variety of pathogenic microorganisms, even at low concentrations (Lin et al 2000;Luciano and Holley 2009). The potential of AITC as a natural antimicrobial has been shown in different foods, including chicken breast (Shin et al 2010), ground beef (Chacon et al 2006a;Nadarajah et al 2005), dry-cured ham (Graumann and Holley 2007), fermented dry sausages (Chacon et al 2006b) and tuna meat (Hasegawa et al 1999). The goals of this study were to study a) the qualiquantitative GLCs composition of yellow and oriental mustard flours and b) the reduction of AFs production by A. parasiticus in wheat tortilla treated with ITCs generated from mustard flours.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been demonstrated that allyl ITC (AITC), which is formed from sinigrin (2-propenyl glucosinolate), effectively inhibits a variety of pathogenic microorganisms, even at low concentrations (Lin et al 2000;Luciano and Holley 2009). The potential of AITC as a natural antimicrobial has been shown in different foods, including chicken breast (Shin et al 2010), ground beef (Chacon et al 2006a;Nadarajah et al 2005), dry-cured ham (Graumann and Holley 2007), fermented dry sausages (Chacon et al 2006b) and tuna meat (Hasegawa et al 1999). The goals of this study were to study a) the qualiquantitative GLCs composition of yellow and oriental mustard flours and b) the reduction of AFs production by A. parasiticus in wheat tortilla treated with ITCs generated from mustard flours.…”
Section: Introductionmentioning
confidence: 99%
“…1a) is a major pungent, an antimicrobial compound found in cabbage, horseradish, mustard, wasabia and used in food packaging [24], and biomedical applications [25,26]. IC of AITC with CD was investigated in the literature [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ITCs have also been reported to display anticancer activity in humans (12). Because of the antimicrobial and anticancer properties of ITCs, several studies have proposed the use of ITCs as food preservatives (11,(13)(14)(15)(16).…”
mentioning
confidence: 99%